2002
DOI: 10.1103/physrevb.66.092407
|View full text |Cite
|
Sign up to set email alerts
|

Small conductance fluctuations in a second-order colossal magnetoresistive transition

Abstract: Epitaxial films of La 0.72 Sr 0.28 MnO 3 ͑LSMO͒ are found to show almost no excess conductivity fluctuations associated with the colossal-magnetoresistive transition, in contrast to the closely related material La 0.67 Ca 0.33 MnO 3 ͑LCMO͒. The result fits with the contrast between the suspected second-order transition in LSMO and the ͑locally͒ first-order transition and mixed phase in LCMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
10
1
Order By: Relevance
“…For each film thickness the reported α H /n values reported in table 2 are averaged over several 20 and 50 µm wide microbridges of various lengths (50, 100, or 150 µm). α H /n varied from 2.36 × 10 −31 to 3.41 × 10 −30 m 3 , which is among the lowest values reported for epitaxial LSMO films on STO (0 0 1) substrates, thus reaffirming the high quality of all the tested LSMO films [7,10]. We observed that the 1/f noise level in LSMO is slightly lower on STO substrates than on STO/Si substrates.…”
Section: Filmsupporting
confidence: 70%
See 2 more Smart Citations
“…For each film thickness the reported α H /n values reported in table 2 are averaged over several 20 and 50 µm wide microbridges of various lengths (50, 100, or 150 µm). α H /n varied from 2.36 × 10 −31 to 3.41 × 10 −30 m 3 , which is among the lowest values reported for epitaxial LSMO films on STO (0 0 1) substrates, thus reaffirming the high quality of all the tested LSMO films [7,10]. We observed that the 1/f noise level in LSMO is slightly lower on STO substrates than on STO/Si substrates.…”
Section: Filmsupporting
confidence: 70%
“…This result could help us to find some indications about the origin of 1/f noise in LSMO thin films. A wide range of results on lowfrequency noise in LSMO thin films, which are sometimes contradictory, can be found in the literature indeed [6][7][8][9][10][11][12][13][14]. It can be explained by the wide variety of sample geometries and structural properties.…”
Section: Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…A standard transfer-line cryostat was used in an electromagnet, with standard measurement techniques similar to those used in earlier works on manganite films. 7,17,18 The new ablated film was prepared as a simple four-probe bar, with width 3 m, length roughly 20 m, and thickness of about 50 nm. All measurements of both noise and resistance used separate current and voltage contacts.…”
Section: Materials and Techniquesmentioning
confidence: 99%
“…Despite their high figure of merit, TMR junctions based on MgO tunnel barrier often have significant noise compared with GMR [2]. Full spin polarized material like manganite La 0.66 Sr 0.33 MnO 3 (LSMO) are attractive candidates to develop such sensors because LSMO possess a very low 1/f noise when grown on single crystals [3], and a high tunnel magnetoresistance response has been observed with values higher than 100% at 77K [4,5]. Using this kind of tunnel junctions opens possibilities to develop full oxide structures working at liquid nitrogen temperature.…”
Section: Introductionmentioning
confidence: 99%